Effect of Al addition on creep resistance of MgO-Al2O3 composite for sliding plate at 1400 °C. Issue 15 (15th October 2017) - Tong, Shanghao; Li, Yong; Zhao, Jizeng; Yan, Mingwei; Sun, Jialin; Jiang, Peng; Kumar, R. Vasant
Abstract: MgO-Al2 O3 composites were prepared using fused magnesia, α-Al2 O3 micropowder, tubular alumina, metal aluminum and sintered magnesia as raw materials, magnesium aluminate sol as the binder. The creep resistance test was conducted at 1400 °C under 0.2 MPa with insulation for 50 h. The specimens after creep resistance test were characterized and analyzed by XRD, SEM, and EDS to investigate the effect of adding metal aluminum powder on the creep resistance of magnesia based composites as well as its mechanism. The results show that Al-MgO-Al2 O3 composite has better creep resistance than MgO-Al2 O3 composite. Power Al is more reactive than AlN, adding Al function is to accelerate both spinel solid solution(containing MgAlON) and AlN-polytype, both are reinforcement phase for MgO-Al2 O3 composite. The mechanism that metal Al powder improves the creep resistance of the specimen M2 can be expressed as follows：An oxygen concentration gradient exists in the specimen M2 from the external areas to the internal areas. The Al in external areas is oxidized into Al2 O3 and further solid-solves with MgO forming MgAl2 O4 . The oxidation of Al leaves shell structures which can bear some compressive stress, restraining the volume shrinkage. When the oxygen concentration is low, Al is nitrided forming reinforcing phases such as AlN polytype and lamellar-structure MgAlON with reticular distribution, restraining the volume shrinkage of specimen M2 .